Comparative Study of the Mechanical Performance of SKD-11, SKD-61, and ST-41 Steels for Brake Handle Mold Design Using Finite Element Analysis - Reson Wibowo; Nurjaya Nurjaya; Muhammad Aldi Hartadi; Jaja Miharja; Agus Bayu Utama; Ruhama Sidqy (G-Tech: Jurnal Teknologi Terapan, 2026)
This study investigates the mechanical performance of SKD-11, SKD-61, and ST-41 steels for brake handle mold applications using Finite Element Analysis (FEA). The increasing demand for durable and reliable mold materials in automotive manufacturing requires accurate evaluation methods to determine the most suitable steel material. However, comparative studies evaluating industrial steels under identical loading conditions remain limited. The research employed a numerical simulation approach using three-dimensional CAD modeling and static structural analysis. Material properties including Young’s modulus, yield strength, and Poisson’s ratio were assigned to each material. A load of 72,000 N, generated from a pressure of 9 bar acting on a surface area of 0.08 m², was applied to the brake handle mold model. Stress distribution, strain behavior, and safety factor were evaluated for each material.The simulation results indicate that all materials experienced similar stress values due to identical geometry and loading conditions. SKD-11 produced the highest safety factor of 3.05, followed by ST-41 with 2.80, while SKD-61 showed the lowest safety factor of 1.50. The strain values remained within the elastic region for all materials. The findings demonstrate that SKD-11 provides the best structural reliability and mechanical performance for brake handle mold applications. This study confirms that Finite Element Analysis is an effective approach for evaluating material selection in industrial mold design.